DETONATION OF HEAVY HYDROCARBONS IN MANTLE FLOWS - Karpov I.K.; Zubkov V.S.; Bychinskii V.A.; Artimenko M.V. (My University, 1998)
A quantitative thermodynamic model for detonation of metastable accumulations of heavy hydrocarbons ascending from the upper mantle is considered. The Chapman-Jouguet detonation parameters were determined by minimizing the minus-entropy of the C-H system of composition 1:2.1 with a fixed internal energy under isochoric conditions by means of the program complex Selektor-C. It has been established that the energetic capacity of metastable heavy hydrocarbons (MHH) is close to that of trinitrotoluene. It varies in the depth range of 30-90 km and is maximum at a depth of 62 km. The maxima of excessive pressure and temperature resulted from MHH detonation also lie in this range. Depending on the regime of MHH ascension - isothermal or nonisothermal (by a geobarotherm) - and the depth from which a fluid ascends to a detonation focus, at the detonation instant the pressure can reach 210 kbar and the temperature attains 4800°C. Estimates are given for the radii of ball-shaped MHH accumulations, whose detonation may be accompanied by earthquakes with release of energy of 1018-1022 erg.